Corrosion protection of metals by intrinsically conducting polymers - Deshpande, Pravin P.; Sazou, Dimitra (CRC Press LLC, 2016)
"The authors examine strategies to improve CP anticorrosion performance, and describe new formulations of CP-based coatings. They discuss an integrated approach involving principles of chemistry, material science, paint technology and corrosion engineering, and present various methods and techniques for corrosion testing and prevention. They also include case studies provided by Zipperling Kessler and offer input on future research, applications, and trends."--